2002
DOI: 10.1191/0961203302lu138cr
|View full text |Cite
|
Sign up to set email alerts
|

Lung cavitation in primary antiphospholipid syndrome

Abstract: Pulmonary complications of primary antiphospholipid syndrome are common and diverse, with thromboembolic events counting as the most frequent manifestation. We present the case of a female patient with a diagnosis of primary antiphospholipid syndrome, pulmonary thromboembolism and infarction followed by lung cavitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Bertoli et al reported a case of thromboembolic disease with secondary aseptic cavitary lung lesions. 6 Our patient had definite lupus and secondary antiphospholipid syndrome. His cavitary lung lesions resolved after starting the immunosuppressive and antithrombotic treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Bertoli et al reported a case of thromboembolic disease with secondary aseptic cavitary lung lesions. 6 Our patient had definite lupus and secondary antiphospholipid syndrome. His cavitary lung lesions resolved after starting the immunosuppressive and antithrombotic treatment.…”
Section: Discussionmentioning
confidence: 64%
“…In those with collateral arteries, the absence of protective proximal stenosis can trigger focal pulmonary vascular disease, with the propensity for stasis, thrombosis, and haemorrhage. Pulmonary infarction in this setting can result in both aseptic pulmonary cavitation and development of lung abscesses 2 4 This may be similar to the propensity to infection described secondary to micro-infarction in sickle cell anemia 5…”
Section: Discussionmentioning
confidence: 75%
“…25 All of our patients with pulmonary infarction had positive antiphospholipid antibodies fulfilling the diagnostic criteria of definite APS without other risk factors associated with venous thromboembolism or pulmonary embolism, similar to the previously reported patients in the literature. [10][11][12] Nevertheless, hypercoagulability due to nephrotic syndrome in membranous lupus nephritis (cases no. 1 and 3) could contribute to the development of lung infarcts in these reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Furthermore, there were only a few reported cases of lung infarcts in patients with APS. [10][11][12][13] Given that pulmonary infarction has the image feature of lung consolidation which is difficult to differentiate from pneumonia on chest X-rays, and untreated patients are associated with potential mortality, clinically suspected cases demand prompt diagnosis and immediate management. 14 There is a high incidence and prevalence of lupus patients with characteristic presentations of APS in Taiwan.…”
Section: Introductionmentioning
confidence: 99%